Pentingnya Peningkatan Kinerja Pegawai pada Kantor Kelurahan Kepala Dua Wetan Kecamatan Ciracas Jakarta Timur - Husada, Sigit Ardianto (ANTASENA: Governance and Innovation Journal, 2023)
Human Resources (HR) in an organization are people who work in an organization who are often called employees. Human resources are the most valuable asset in government organizations, without human resources the resources in the organization will not be able to produce optimal performance. Employee performance is the work results achieved by employees within a certain period of time to achieve a goal. The aim of this writing is to determine the increase in employee performance at the Head of Dua Wetan Village Office, Ciracas District, East Jakarta. The research results from this paper are that the success of an organization is largely determined by the quality of human resources or the people who work in it. Measuring employee performance at the Head of Dua Wetan Subdistrict Office, Ciracas District, East Jakarta, through: Quality, Quantity, Use of time and Collaboration. Efforts by the Head of Dua Wetan Subdistrict Office, Ciracas District, East Jakarta to improve employee performance are carried out through Sharing Sessions, holding education and training, mental guidance and placing human resources according to organizational needs, consistent enforcement of codes of ethics and/or behavior so that they can continue to develop in line with increasingly high development activity and demands to fulfill public interests.